Les désastres de la guerre : quatre-vingt-cinq eaux-fortes - de Goya, Francisco; Faure, Elie (Paris : Phaidon, 1937)
Bibliotheek Jan Baghus
Frans
Monografie
Keywords: de Goya, Francisco; oorlogsslachtoffers